Pengaruh mekanisme tata kelola perusahaan, pendanaan hutang perusahaan, dividen serta ukuran perusahaan terhadap kualitas laba - SATYA SARAWANA; NICKEN DESTRIANA (Jurnal Bisnis dan Akuntansi, 2015)
The purpose of this study is to investigate the influence of corporate governance mechanism, mainly ownership centralization, board independence, audit committee expertise and audit committee size on earnings quality. This study also employs corporate debt financing, dividend and firm size in order to predict earnings quality. This research used 49 nonfinancial companies listed in Indonesia Stock Exchange. Data were collected through purposive sampling method during the research period 2008-2012. The result of this research showed that board independence and governance expertise of audit committee have influence toward earnings persistence as a measure of earnings quality. This result indicate that the existing of board independence and governance expertise of audit committee can improve the quality of earnings.